Biomechanical evaluation of custom-made short implants with wing retention applied in severe atrophic maxillary posterior region restoration: A three-dimensional finite element analysis - Zhen Yang; Zhen Yang; Jingran Zhang; Jingran Zhang; Zexian Xu; Zexian Xu; Xiaoqiang Liu; Xiaoqiang Liu; Jianjun Yang; Jianjun Yang; Jianguo Tan; Jianguo Tan (Frontiers in Bioengineering and Biotechnology, 2023)
Severe bone atrophy in the maxillary posterior region poses a big challenge to implant restoration. Digitally designed and customized short implants with wing retention provide a safer and minimally invasive implant restoration scheme in such circumstances. Small titanium wings are integrated with the short implant supporting the prosthesis. Using digital designing and processing technology, the wings fixed by titanium screws can be flexibly designed, providing the main fixation. The design of the wings will influence the stress distribution and implant stability. This study analyzes the position, structure, and spread area of the wings fixture scientifically by means of three-dimensional finite element analysis. The design of the wings is set to linear, triangular, and planar styles. Under the simulated vertical and oblique occlusal forces, the implant displacement and stress between the implant and the bone surface are analyzed at different bone heights of 1 mm, 2 mm, and 3 mm. The finite element results show that the planar form can better disperse the stress. By adjusting the cusp slope to reduce the influence of lateral force, short implants with planar wing fixtures can be used safely even if the residual bone height is only 1 mm. The results of the study provide a scientific basis for the clinical application of this new customized implant.